PENERAPAN BIAYA TRANSPORTASI PENDISTRIBUSIAN ALAT SWAB TEST COVID-19 MENGGUNAKAN METODE LEAST COST DAN LINGO - Robby Rahmansah (LPPM Universitas Bina Bangsa, 2021)
Optimization of distribution transportation costs of PT. Batara Husindo Raya aims to obtain optimal transportation costs in the distribution of the Covid-19 Swab Test Tool from agents to hospitals. The application of the initial solution of the transportation model using the Least Cost method and determining the optimal solution using the Lingo method. From the calculation results obtained the initial solution of . 120,000,000 and the optimal solution is . 120,000,000. This shows that the calculation using the lowest cost method and the term to produce the same optimal value